2012
DOI: 10.3171/2011.10.jns11261
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of longitudinal synchrony of epileptiform discharges in the hippocampus for seizure generation: a pilot study

Abstract: These data suggest that synchronized discharges involving the complete anterior-posterior axis of the hippocampal/parahippocampal (H/P) formation underlie the spread of epileptiform discharges outside the H/P structures and, therefore, for the generation of epileptic seizures originating in the H/P structures. This conclusion is supported by the following observations. 1) Hippocampal spikes are consistently synchronized in the whole hippocampal structures, with a fixed delay between the different hippocampal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Although the role of the VH in the generation of epileptiform activity (EA) is significant, the importance of connections between DH and VH for full seizure development should not be underestimated. Recent clinical and basic research studies show that hippocampal longitudinal synchrony of EA is required for seizure generation and transection of the hippocampal longitudinal epileptic circuits is effective in suppressing seizures (Imamura et al, 2001; Shimizu et al, 2006; Umeoka et al, 2012). However the premise for the increase of hippocampal longitudinal synchronization in epileptic brain is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of the VH in the generation of epileptiform activity (EA) is significant, the importance of connections between DH and VH for full seizure development should not be underestimated. Recent clinical and basic research studies show that hippocampal longitudinal synchrony of EA is required for seizure generation and transection of the hippocampal longitudinal epileptic circuits is effective in suppressing seizures (Imamura et al, 2001; Shimizu et al, 2006; Umeoka et al, 2012). However the premise for the increase of hippocampal longitudinal synchronization in epileptic brain is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the EEG recording is the optimal method to study neuronal bioelectrical activity [20]. During ictal and interictal periods, there are over-synchronized discharges in the cerebral cortex [21]. Furthermore, it has been shown that EEG recordings demonstrate that kainic acid-induced epilepsy is a useful model for epilepsy research [22].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Although the concept of HT was a proposed hypothesis, not an accepted doctrine, recent studies have described detailed electrophysiological observations in humans 25 and memory preservation in rat models 12 that support the theory and efficacy of HT. However, in the previous literature, the important processes of the surgery and the depth and extent of transection were ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…15,25 On the other hand, we modified the original HT approach and adopted a transsylvian approach to access the inferior horn of the lateral ventricle. In the transsylvian approach, there are some potential risks of cortical damage to the temporal and frontal opercula when splitting the sylvian fissure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation